Open innovation in digital healthcare: Users' discrimination between certified and non-certified mHealth applications - Ana Gessa; Amor Jiménez; Pilar Sancha (Journal of Open Innovation: Technology, Market, and Complexity, 2020)
Mobile applications users consider it especially important to have quality certification, and particularly in an e-health context. However, if the app is certified, will user satisfaction be greater? This paper is intended to help answer that question. Therefore, with user satisfaction as a determinant of the quality of services, the purpose of the paper is to understand the extent to which certified and non-certified mHealth apps influence user experience. This was measured by online reviews and downloads. An empirical study was carried out with 50 mHealth apps (21 certified, 29 non-certified), which is a convenient sampling procedure. The Mahalanobis matching technique was used to test for significant differences between the groups. A comparative content analysis was performed on 6188 user comments and on app downloads. Non-parametric tests were preferred because the variables analyzed had a categorical structure. A log-linear model and advanced contingency tables were used to examine the more than two-way relationships of variables. The results show differences between the two samples (certified and non-certified mHealth apps). However, quality certification labels as a guarantee of the quality of apps do not have a modulating effect on the online reviews and downloads relationship. The model showed a statistically significant partial association between "certification" and "online user reviews" (Z = 2.174; sig = 0.042)] and between "download" and "online user reviews" (Z = 2.387; sig = 0.017).
Keywords: 650; appsaludable; certification; health mobile applications; online user review; quality; quality seal; user experience